EARNINGS PER SHARE, INFLATION, AND NET INTEREST MARGIN AS STOCK PRICE ANTECEDENTS IN THE BANKING SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2019-2021 PERIOD - Rosa Ariana; Salamatun Asakdiyah; Aftoni Sutanto (Jurnal Scientia, 2023)
Banking is one of the companies that has an important role in supporting the economy. This study aims to observe financial performance. Thus the results of this study are intended to determine the effect of Earnings Per Share, Inflation and Net Interest Margin on the Stock Price of the banking sector. This type of research uses quantitative because the use of data is in the form of numbers. Data acquisition is secondary in financial statements. population use, namely the listing as a whole on the Indonesia Stock Exchange specifically for the 2019-2021 period. Purposive sampling through certain criteria. The number of samples produced was 38 banks in three years. Data processing using panel data regression analysis techniques through Eviews. This test provides results that the first hypothesis of Earnings Per Share has a significant influence on the stock price of the banking sector, the second hypothesis of Inflation does not have a significant effect on the stock price of the banking sector and the third hypothesis of Net Interest Margin does not have a significant effect on the stock price of the banking sector.